Estudos preliminares de análise de ativação cerebral em pacientes com surdez neurossensorial e zumbido submetidos à estimulação galvânica vestibulococlear durante RMf - Buffon, Graziela Giacometti Fermino (2018)
This study addressed the issue of the use of vestibulocochlear galvanic stimulation (VCGS) in female patients, aged between 60 and 75 years old, with tinnitus associated with sensorineural hearing loss, uni or bilateral, of degree mild to moderate and submitted to functional magnetic resonance imaging (fMRI). The objective of this study was to identify the brain areas activated during the stimulation process, the brain mapping from fMRI technology and respective statistical data analysis. The methodology of this research was the qualitative and quantitative data analysis, through the experimental and exploratory-descriptive method of the test and the theoretical reference of the art study. The patients were duly selected in a public health institution in Curitiba, which was submitted to the Research Ethics Committee. The RMF exams were performed in partnership with the study's co-participant. Statistical Parametric Mapping (SPM) software was used for analysis in MATLAB. The results showed that electro stimulation activated the auditory cortex in 40% of the patients and that there is a possibility that tinnitus is closely related to the limbic system and not just auditory. In addition, the results refer to: contralateral left hemisphere (more activated) and tinnitus and PANS complaints in the right ear; the non-activation of the pre-cuneus in the patient with a longer tinnitus time (default neural network); to the non-activation of the cerebellum (vestibulocerebellum) in all patients. It was not possible to make a concise relate the age, time with tinnitus and the type of PANS with the activated areas. This study elucidated the hypothesis that brain areas are activated after electrostimulation with galvanic current in the selected patients and the analysis of brain activation can serve as a guide for health professionals to understand if there is a relationship between tinnitus improvement and the use of VCGS and knowledge of the activated areas and the correlation between them may serve as motivation for other studies.